Efficacy of translation in the rickettsia Coxiella burnetii. - Donahue, J P (1981)
The addition of coliphage Q beta ribonucleic acid to a cell-free translation system obtained from Coxiella burnetii cells caused the formation of monosomes and disomes from ribosomal subunits and resulted in synthesis of viral coat protein. Rickettsial ribosomes and associated translation factors functioned together, with fidelity, efficiency, and a specificity similar to those of free-living gram-negative bacteria.